A new lateral root growth inhibitor from the sponge-derived fungus Aspergillus sp. LS45. Issue 13 (1st July 2019) - Huang, Liming; Ding, Lijian; Li, Xiaohui; Wang, Ning; Yan, Yushan; Yang, Mengxiang; Cui, Wei; Benjamin Naman, C.; Cheng, Kejun; Zhang, Weiyan; Zhang, Bin; Jin, Haixiao; et al.
Graphical abstract: Highlights: Two new lactones (1 and2 ) and two known (3 and4 ) were discovered from a culture of the marine sponge-associated fungus. The structures were characterized by comprehensive spectroscopic methods. Compounds1 and4 exhibited significant inhibition against the lateral root growth of Arabidopsis thaliana Columbia-0. Compound4 showed moderate inhibitory effects on CCRF-CEM and K562 cancer cell lines. Abstract: Two new γ -lactones, aspergilactones A (1 ) and B (2 ), were discovered along with two known compounds, annularin A (3 ) and pericoterpenoid A (4 ), from a culture of the sponge-associated fungus Aspergillus sp. LS45. The planar structures of1 –4 were characterized using comprehensive spectroscopic methods and comparison with literature data. The absolute configurations of1 and2 were determined by comparison of electronic circular dichroism (ECD) spectroscopic and optical rotation data with those of known analogues as well as calculated ECD analysis. Compounds1 –4 were tested in a variety of bioassays, and both1 and4 exhibited significant inhibition against the lateral root growth of Arabidopsis thaliana Columbia-0 at a concentration of 100 μM. In addition, the in vitro cytotoxic activities of1 –4 against six human cancer cell lines CCRF-CEM, K562, BGC823, AGS, HCT-116 and MDA-MB-231 were evaluated. Compound4 showed moderate inhibitory effects on CCRF-CEM and K562 cancer cell lines with IC50 values of 13.8 ± 1.6 and 12.9 ± 2.5 μM, respectively. However, compounds1 –4 did not show any notable AChE inhibitory activity in vitro .